Synthesis of 4-phenyloxazinones via DBU-catalyzed cleavage of 4-bromomethylcoumarins. Issue 2 (17th January 2017) - Shamala, Devadas; Shivashankar, Kalegowda
ABSTRACT: A new route for ring transformation has been discovered during the reaction of 4-bromomethylcoumarins with hydroxyl amine in the presence of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU), leading to the formation of pharmacologically important 1, 2-oxazinones in a single step with very high yields. GRAPHICAL ABSTRACT: